Jaipur 1778: the making of a king - Horstmann, Monika (Harrassowitz Verlag, 2014)
Jaipur 1778 narrates the interregnum concluded with the royal consecration of Pratapsingh (1778-1803). Over the period of a month, the new king became vested with the power of symbols that legitimated his dynasty. To the extent that this was a process taking place in the public space, it also confirmed the symbolic structure of the two royal residences involved. Monika Horstmann's book examines the history of those symbols and their human agents and the public ritual performed. The "Kingdom of Jaipur", "Funeral and Mourning", "Processions" as well as the "Royal Consecration" are analysed. A co
Description based upon print version of record
Keywords: Electronic books; Geschichte 1778; Symbol; Ritual; Königsweihe; Maharadscha; Jaipur